Build it: A Feasibility Study of GIS-Based Analyses of Cycling Infrastructure - Thistle, Ian. (2017)
Abstract: Cycling for everyday transportation provides a myriad of benefits to communities. To increase their cycling levels, cities have looked to infrastructure and design strategies first used in Europe, especially physically separated bike lanes. Implementation of these designs has helped increase cycling modeshare in U.S. cities; however, limited government resources make efficient and accurate evaluation of infrastructure problematic. This thesis explores multiple GIS-based methods for evaluating road infrastructure for cycling, and tests their feasibility for replication. Two previously published GIS-based methods are replicated for a representative sample of Somerville and Cambridge, MA. The sample is also "ground truthed" by volunteers using the methods' criteria, and results compared to the GIS analyses. It was found that while both methods were technically feasible and compared reasonably well to real-world conditions, there were deficiencies that would increase the labor involved to verify either analysis in practice. Recommendations to improve these methods are discussed.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Mary Davis.; Committee: Barbara Parmenter.; Keywords: Transportation, Urban planning, and Geographic information science and geodesy.